Factors affecting the responses of female Canada Geese to disturbance during incubation. Issue 2 (27th May 2013) - Miller, Valerie; Abraham, Kenneth F.; Nol, Erica
ABSTRACT During incubation, Canada Geese (Branta canadensis) and other waterfowl flush from their nests in response to the approach of potential predators and subsequently return to nests after the threat of predation has abated. Differences among individuals in their responses to such disturbance (e.g., how close a potential predator approaches before flushing) are thought to reflect variation in female age, the reproductive value of clutches, and nest site characteristics. From 26 April to 26 May 2010, we examined the possible effects of these factors on the behavior of female Canada Geese (B. c. interior) on Akimiski Island, Nunavut. We used humans as surrogate predators and flushing distance and return time after disturbance as response variables. The distance at which females flushed in response to approaching humans was best explained by the density of vegetation around nests, with females on better concealed nests flushing at closer distances. We also found a weak relationship between return time and clutch size, with females with larger clutches returning to nests sooner. The frequency of human visits did not affect either female flushing distance or return time. Female Canada Geese in our study appeared to minimize risk of their own injury or death (future reproductive potential) in escape decisions, whereas return times appeared to minimize the risk of nest predation (current reproductive investment).